COVID-19, 2020 Prosperity Gospel, and Belief in Prophetic Churches in Nigeria: Repositioning Perspectives - Orukpe, Williams E. (Journal of Living Together, 2023)
The coronavirus pandemic was a ravaging storm cloud with silver lining. It took the world by surprise and left mixed actions and reactions in its wake. COVID-19 in Nigeria went down in history as a public health crisis that triggered a religious renaissance. It shook Nigeria’s health care system and prophetic churches to their foundation. This paper problematizes the failure of the December 2019 prosperity prophecy for 2020. Using the historical research method, it corroborates primary and secondary data to demonstrate the impact of the failed 2020 prosperity gospel on social interactions and belief in prophetic churches. It finds that out of all the organized religions operational in Nigeria, prophetic churches are the most attractive. Prior to COVID-19, they stood tall as acclaimed healing centers, seers, and breakers of evil yoke. And belief in the potency of their prophecies was strong and unshakable. On December 31, 2019, both staunch and irregular Christians made it a date with prophets and pastors to obtain New Year prophetic messages. They prayed their way into 2020, casting and averting all supposed forces of evil deployed to hinder their prosperity. They sowed seeds through offering and tithing to back their beliefs. Resultantly, during the pandemic some staunch believers in prophetic churches cruised under the prophetic delusion that coverage by the blood of Jesus builds immunity and inoculation against COVID-19. In a highly prophetic environment, some Nigerians wonder: how come no prophet saw COVID-19 coming? Why were they unable to heal any COVID-19 patient? These thoughts are repositioning beliefs in prophetic churches in Nigeria.
free